Functional correction of the student's state by means of special branch of educational recreational walking and running. - Gatsko E.V (Kharkov National Pedagogical University, 2012)
Resulted taking in relation to application of author method of the use of facilities of the health walking and at run. In an experiment took part 175 students at the age 17-20. The series of researches contained 160 hours in a year (for 32 employments in the I II semester and 1 hour for a week independent employments). Middle volume of the physical loading - 50-55% maximal consumption of oxygen (pulse of 120-130 stroke / minute). For students with the satisfactory level of physical capacity foreseen health walking with alternation at health run. Middle volume of the physical loading - 55-70% maximal consumption of oxygen (pulse of 135-150 stroke / minute). The functional state and level of physical development of students is appraised with a vegetative vascular dystonia with the complicated pathology of sight. The size of loading is certain in the health walking and at run for students with the low and satisfactory level of physical capacity. The necessity of including of the health walking and at run is set for employments on physical education. It is discovered that insufficiency of the aerobic loading conduces to the decline of health effect of employments in physical education.